Direct determination of arsenobetaine and total As in robalo fish liver and tuna fish candidate reference material by slurry sampling graphite furnace atomic absorption spectrometry (SLS-GF AAS) - Bossu, Carla Maíra [UNESP]; De Oca Carioni, Vivian Montes; Naozuka, Juliana; De Oliveira, Pedro Vitoriano; Nomura, Cassiana Seimi (My University, 2019)
This work describes a simple and rapid screening method for direct speciation of arsenobetaine (AsB) in tuna fish tissue and total As in tuna fish tissue and robalo liver using SLS-GF AAS. All procedures were proposed after careful optimization of pyrolysis and evaluation of chemical modifiers. Best results for total As were acquired using 25 μg Pd + 15 μg Mg + 0.1% w/v Triton X-100 in tuna fish (4.4 ± 0.3 mg kg-1) and 100 μg Pd + 0.1 % w/v Triton X-100 solution in robalo liver (10.3 ± 0.6 mg kg-1) as chemical modifiers. The direct speciation of AsB (3.6 ± 0.4 mg kg-1) in tuna fish was achieved when 5 μg Pd + 3 μg Mg + 0.1% w/v Triton X-100 was used as a chemical modifier. Accuracy was verified using a tuna fish certified reference material (CRM BCR 627), with statistically equivalent concentrations (Student's t-test) for both total As and AsB.
Keywords: 1. arsenic 2. direct chemical speciation 3. tuna fish 4. robalo liver 5. reference material